Inicialne združbe na prodiščih reke Nadiže v zahodni Sloveniji (asociacija Epilobio-Scrophularietum caninae W. Koch & Br.-Bl. ex Müller 1974) - Čušin, Boško (Hladnikia (Ljubljana), 2001)
The article presents the research of the initial communities on the gravel-banks of the Nadiža river in western Slovenia. After comparing them to similar communities in the neighbouring Friuli (NE Italy) and elsewhere in the Centra-European area, we classified them into a new subassociation Epilobio-Scrophularietum caninae W. Koch & Br. Bl. ex Müller 1974 petasitetosum paradoxi subass. nova. Its differential species are Petasites paradoxus and Achnatherum calamagrostis.
Keywords: fitocenologija; gozdne združbe; Nadiža; Natisone; phytosociology; Slovenia; Slovenija